2016
DOI: 10.1038/srep33289
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein is a Novel Microtubule Dynamase

Abstract: α-Synuclein is a presynaptic protein associated to Parkinson’s disease, which is unstructured when free in the cytoplasm and adopts α helical conformation when bound to vesicles. After decades of intense studies, α-Synuclein physiology is still difficult to clear up due to its interaction with multiple partners and its involvement in a pletora of neuronal functions. Here, we looked at the remarkably neglected interplay between α-Synuclein and microtubules, which potentially impacts on synaptic functionality. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 55 publications
6
99
0
Order By: Relevance
“…The staining of pSer129 + inclusions with the Proteostat aggresomal dye is consistent with previous studies on similarities between Lewy bodies and aggresomes (112,161). The formation of the aggresome is microtubule-dependent (96) and α-synuclein appears to interact with tubulin, perhaps serving as a microtubule dynamase (6,37,135). Aggresomes are hypothesized to serve as a protective mechanism facilitating cellular survival under proteotoxic conditions (162), as they are observed in 53%-60% of nonapoptotic cells but only 10%-13% of apoptotic cells in vitro (161).…”
Section: α-Synucleinopathic Inclusions In the Preformed Fibril Model supporting
confidence: 89%
“…The staining of pSer129 + inclusions with the Proteostat aggresomal dye is consistent with previous studies on similarities between Lewy bodies and aggresomes (112,161). The formation of the aggresome is microtubule-dependent (96) and α-synuclein appears to interact with tubulin, perhaps serving as a microtubule dynamase (6,37,135). Aggresomes are hypothesized to serve as a protective mechanism facilitating cellular survival under proteotoxic conditions (162), as they are observed in 53%-60% of nonapoptotic cells but only 10%-13% of apoptotic cells in vitro (161).…”
Section: α-Synucleinopathic Inclusions In the Preformed Fibril Model supporting
confidence: 89%
“…In the present study, we observed enhanced miR-17-5p expression and concomitant reduction of its target Map6 in the colonic MP of psA30P mice, suggesting that miR-17-5p-mediated regulation of Map6 could be involved in the initiation of PD pathogenesis. Interestingly, α-synuclein interacts with microtubules in HeLa cells 89 and preferably with tyrosinated tubulin in human mesencephalic neurons 90 . In agreement with our in vitro results, A30P α-synucleins regulate the microtubule network in PD.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the identification of familial cases with multiplications of SNCA (the gene encoding for α‐syn) revealed a strong correlation between α‐syn accumulation and aggregation, and disease severity . Although the physiological role of α‐syn is not fully characterized, it has been shown that it plays important roles in the supply of synaptic vesicles in presynaptic terminals and in the movement of microtubules …”
Section: Mutations In Genes Encoding Autophagic‐lysosomal Proteins Inmentioning
confidence: 99%
“…[23][24][25] Although the physiological role of α-syn is not fully characterized, it has been shown that it plays important roles in the supply of synaptic vesicles in presynaptic terminals 26,27 and in the movement of microtubules. 28,29 VPS35 encodes vacuolar protein sorting-associated protein 35, which is involved in the endosomal-lysosomal trafficking associated to autophagy. Mutations on VPS35 cause a rare form of autosomal-dominant PD.…”
Section: Mutations In Genes Encoding Autophagic-lysosomal Proteinsmentioning
confidence: 99%